Phylogenomic Analyses of Non-Dikarya Fungi Supports Horizontal Gene Transfer Driving Diversification of Secondary Metabolism in the Amphibian Gastrointestinal Symbiont, Basidiobolus. Issue 9 (1st September 2020) - Tabima, Javier F; Trautman, Ian A; Chang, Ying; Wang, Yan; Mondo, Stephen; Kuo, Alan; Salamov, Asaf; Grigoriev, Igor V; Stajich, Jason E; Spatafora, Joseph W
Abstract: Research into secondary metabolism (SM) production by fungi has resulted in the discovery of diverse, biologically active compounds with significant medicinal applications. The fungi rich in SM production are taxonomically concentrated in the subkingdom Dikarya, which comprises the phyla Ascomycota and Basidiomycota. Here, we explore the potential for SM production in Mucoromycota and Zoopagomycota, two phyla of nonflagellated fungi that are not members of Dikarya, by predicting and identifying core genes and gene clusters involved in SM. The majority of non-Dikarya have few genes and gene clusters involved in SM production except for the amphibian gut symbionts in the genus Basidiobolus . Basidiobolus genomes exhibit an enrichment of SM genes involved in siderophore, surfactin-like, and terpene cyclase production, all these with evidence of constitutive gene expression. Gene expression and chemical assays also confirm that Basidiobolus has significant siderophore activity. The expansion of SMs in Basidiobolus are partially due to horizontal gene transfer from bacteria, likely as a consequence of its ecology as an amphibian gut endosymbiont.